2001
DOI: 10.1007/s100290100013
|View full text |Cite
|
Sign up to set email alerts
|

Use of polypropylene prostheses for strangulated inguinal and incisional hernias

Abstract: We used monofilament polypropylene prostheses in 20 emergency operations for strangulated hernias. Sixteen of the operated patients had groin hernias (five of them recurrent), two had incisional and one had a Spigel's type hernia. Intestinal resection was performed because of bowel wall necrosis in one of the patients. During the postoperative period, we observed only one minor complication (a seroma formation). During the follow-up, no recurrence was observed. In our opinion, the use of monofilament polypropy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(10 citation statements)
references
References 0 publications
1
9
0
Order By: Relevance
“…Most surgeons are afraid of wellknown complications that could be associated with foreign material implantation in the setting of incarcerated or strangulated bowel loop. This issue has been studied only in few articles, and either no synthetic material has been used in most of the hernioplasty procedures or very few intestinal resections have been performed in the study groups [1][2][3]. For this reason, we aimed to audit the outcome of acutely incarcerated groin hernias treated by non-absorbable mesh.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Most surgeons are afraid of wellknown complications that could be associated with foreign material implantation in the setting of incarcerated or strangulated bowel loop. This issue has been studied only in few articles, and either no synthetic material has been used in most of the hernioplasty procedures or very few intestinal resections have been performed in the study groups [1][2][3]. For this reason, we aimed to audit the outcome of acutely incarcerated groin hernias treated by non-absorbable mesh.…”
Section: Discussionmentioning
confidence: 98%
“…Delving into related literature, there can be seen a few articles regarding herniorrhaphy under emergent conditions. Thus, mesh usage in the presence of intestinal necrosis has not been investigated adequately [1][2][3][4]. This is a crucial issue because the presence of strangulated hernia is a serious clinical condition that is responsible for the significant mortality and requires tension-free and sound repair.…”
Section: Introductionmentioning
confidence: 98%
“…Researchers have published a variety of small-scale studies comparing mesh use to suture repair in the treatment of acute irreducible hernias [43-46]. In 2011, Nieuwenhuizen et al published a retrospective study investigating the use of mesh in acute hernia-related procedures.…”
Section: Recommendationsmentioning
confidence: 99%
“…Second, using a prosthetic substance like prolene mesh as an onlay patch in the emergency treatment of the incarcerated PUH is risk-free, simple to carry out, and not linked to significant systemic or mesh-related problems. Finally, as previously demonstrated by others [12][13][14][15] , intestinal ischemia or necrosis, and subsequent need for the intestinal resection may not be considered contra indications for the mesh repair.…”
Section: Discussionmentioning
confidence: 73%
“…Some studies have shown that prosthetic repair for incarcerated PUH in the emergency settings have yielded good outcomes. [11][12][13][14][15][16] Pre-peritoneal prosthetic mesh was inserted successfully into 35 patients with strangulated groin hernias by Pans et al 12 Polypropylene meshes was used successfully by Wysocki et al to treat strangulated inguinal and incisional hernias. 14 Patients received Lichtenstein treatment for incarcerated groin hernias in a later report by the same group.…”
Section: Discussionmentioning
confidence: 99%